Functional and Cooking Properties of Pasta Fortified with Jackfruit Seed Flour - , V. Anusha; , M. Kirthy Reddy; , M. Poorvitha; , Rita Narayanan (Archives of Current Research International, 2025)
The aim of this study is to develop a functional pasta by partial substitution of refined wheat flour with corn flour and jackfruit seed flour. The impact of replacing refined wheat flour with jackfruit seed flour on the functional properties of pasta was examined. RWF: CF: JFSF were supplemented in the ratio of 80:10:10 and 70:10:20. Cooking characteristics such as optimum cooking time, cooking loss, swelling index and functional properties such as water solubility index, water absorption capacity, bulk density was observed and compared with control. Addition of jackfruit seed flour to the sample significantly changed the functional characteristics of the pasta. An increase in JFSF quantity from control to T2 resulted in a reduction in optimum cooking time from 7.16 to 5.11 min and cooking loss from 9.25 to 5.68%. The swelling index, water solubility index and water absorption capacity were increased from 2.63 to 4.91%, 3.36 to 4.79% and 2.09 to 2062% respectively. In case of bulk density, no significant difference was noted (0.314 to 0.323 g/ml). Therefore, incorporation of jackfruit seed flour into pasta could be a promising way for developing protein-rich, high-quality pasta with improved nutritional and functional properties.